Sustained Content Language Teaching: Insights from an ESL and EFL course - Reynolds, Barry Lee; Shieh, Jin-Jy; Ding, Chen; Ha, Xuan Van (International Journal of English Studies, 2022)
Instructional settings (English as a second language (ESL) and English as a foreign language (EFL)) may provide different opportunities for learners’ meaningful language use. This qualitative study was designed to shed light on this issue. The data included multiple sources collected from a sustained content gastronomy language course taught in an American ESL and a Taiwanese EFL context. Findings revealed that various factors (e.g., themes, environment, and learners) contributed to learners from both contexts meeting course goals. The findings further indicate that it is not the ESL/EFL context but instead using a sustained content language teaching approach that incorporates theme-based instruction and dynamic units that ensures learners are provided opportunities for meaningful and purposeful language use.